Factors of depression: evidence from 15 Asia countries / Nur Syazwani Zakaria - Zakaria, Nur Syazwani (2019)
This study was focused on the factors of depression in the 15 Asia countries. Measurement was done on several independent variables consists of four variables which was chronic pain, cyber bullying, unemployment, and compensation to employees will impact on depression. Depression data were retrieved from year 2008 to 2017 (10 years). These data were collected in 15 countries in Asia includes in East Asia (Japan), South Asia (Sri Lanka), Southeast Asia (Malaysia), and West Asia (Afghanistan). Hence, this study used the secondary data to collect the data. The data were collected from four websites which is World Bank Development Database, World Development Indicator (WDI) and Our World in Data which utilize for the period of the 10 year (2008-2017). After collected all the data, it has been analysed into a panel data set encoded in STATA SE 14.0. Type of study used in this research is a casual study. It is undertaken to measure the relationship between the variables. As for this research, represents by percentage of unemployment of total labor force for unemployment rate, DALYs for chronic pain, number of internet users for cyber bullying, and compensation of employees for compensation received by employees on depression. The results show that chronic pain represented by DALYs and compensation of employees have a statistically significant relationship with percentage of depression cases. The results also suggest that chronic pain represented by DALYs is negatively related to the percentage of depression over population, whereas compensation of employees is positively related to the dv. In meanwhile, unemployment and cyber bullying represented by number of internet users do not appear to be significantly related to the percentage of depression cases over population.